Academic Numeracies Framework: A tool to embed numeracy in university curricula - Salmeron, Raquel; Howarth, Debi; Galligan, Linda (Journal of Academic Language and Learning, 2026)
This paper introduces an Academic Numeracies Framework (‘Framework’), designed to support the systematic embedding of academic numeracy across tertiary institutions. The Framework responds to challenges in aligning student numeracy with curricula and to the often-fragmented numeracy development practices in universities. Distinctive features include its focus on tertiary education, its purpose as a teaching and learning tool rather than an assessment instrument, and its multidisciplinary applicability. These features make it an ideal tool to facilitate numeracy embedding across universities. A key application is the mapping of target, assumed and actual student numeracy, informing curriculum design and development, and learning-support initiatives. The paper outlines the Framework’s conceptual foundations, describes its structure and key features, and explains how feedback from first-year and pathway academics, learning development staff and academic managers (educators) informed its refinement. An illustrative application for the nursing discipline is presented. The insights gained position the Framework as a timely and practical tool to guide educators seeking a structured approach to integrate numeracy development into courses, programs and initiatives.